Implementation Marketing Mix Strategy for Local Minimarket Facing on National Chain Store: Case PT Noor Halal Minimarket - Ahmad Nuh; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Diana Fajarwati (Penerbit Kemala Indonesia, 2020)
The increasing business of the national minimarket companies such as local retail in Indonesia (Indomaret and Alfamart) owned by large companies at this time the conventional stores and local minimarkets decrease their competitiveness. Those largest minimarket companies have penetrated their stores in many cities in Indonesia with a modern store operating system, a complete variety of products and surely with the big capital, makes the national minimarkets accepted by the market and faster to open their new stores. This Competition makes the local minimarket have to face challenges with the national minimarket network. The local minimarket must have a strong analysis to win this competition and become the next national minimarket level. Thus, in this study we explore the concept of 4P (Product, Place, Price, Promotion) of the marketing mix, how to operate, where the business will go, and who should be involved in Noor halal Minimarket. This minimarket is a local market in Bogor, West Java with implemented a marketing strategy starts with analyzing the overall situation of the company. The Local minimarket must do a SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) in the company as a whole seller. Besides SWOT, Segmenting, Positioning is also needed to classify the market to be targeted. Here, the SWOT analysis can be used to understand the business mechanism of the company to be a better condition and also be competitive for the company's strength and prevent threats.